The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/spectrum.01782-21
|View full text |Cite
|
Sign up to set email alerts
|

Net Charges of the Ribosomal Proteins of the S10 and spc Clusters of Halophiles Are Inversely Related to the Degree of Halotolerance

Abstract: The net charges (at pH 7.4) of the ribosomal proteins (r-proteins) that comprise the S10-spc cluster show an inverse relationship with the halophilicity/halotolerance levels in both bacteria and archaea. In non-halophilic bacteria, the S10-spc cluster r-proteins are generally basic (positively charged), while the rest of the proteomes in these strains are generally acidic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…Classical operons are found to occur in both Bacteria and Archaea [84,85]. The conservation of the arrangement of the r-protein gene cluster is in congruence with how they are conserved in sequence [21,22,55]. A large chunk of 14 genes from the most highly conserved S10-spc cluster of r-protein coding genes was thus found to be similarly conserved in arrangement, whether it was Bacteria, Asgard, or non-Asgard Archaea.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Classical operons are found to occur in both Bacteria and Archaea [84,85]. The conservation of the arrangement of the r-protein gene cluster is in congruence with how they are conserved in sequence [21,22,55]. A large chunk of 14 genes from the most highly conserved S10-spc cluster of r-protein coding genes was thus found to be similarly conserved in arrangement, whether it was Bacteria, Asgard, or non-Asgard Archaea.…”
Section: Discussionmentioning
confidence: 73%
“…In general, we will refer to them as clusters with the implication that many of them could likely be operons. The S10 and the spc operons (clusters) are the largest, each typically encoding ten-twelve r-proteins [21,22]. Gene expression when known is frequently regulated by one of the r-protein components within the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…As an outcome of such active engagement in EPO, such experiences have helped in maintaining a strong track record of supporting and mentoring minority, high school, undergraduate, and beginning graduate students. When their contributions have been substantial, they have been included as co-authors in peer-reviewed publications ( 41 , 42 , 56 , 60 , 61 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that ribosomal genes contain some information about a given organism’s optimal growth temperature and halotolerance ( 13–23 ). For instance, thermophilic ribosomal proteins were found to have a higher content of certain amino acids, such as arginine, isoleucine, proline and tyrosine, and a decreased content of serine and threonine.…”
Section: Introductionmentioning
confidence: 99%